Molecular basis of differential adventitious rooting competence in poplar genotypes. (24th March 2022) - Ranjan, Alok; Perrone, Irene; Alallaq, Sanaria; Singh, Rajesh; Rigal, Adeline; Brunoni, Federica; Chitarra, Walter; Guinet, Frederic; Kohler, Annegret; Martin, Francis; Street, Nathaniel R; Bhalerao, Rishikesh; et al.
Abstract: Recalcitrant adventitious root (AR) development is a major hurdle in propagating commercially important woody plants. Although significant progress has been made to identify genes involved in subsequent steps of AR development, the molecular basis of differences in apparent recalcitrance to form AR between easy-to-root and difficult-to-root genotypes remains unknown. To address this, we generated cambium tissue-specific transcriptomic data from stem cuttings of hybrid aspen, T89 (difficult-to-root) and hybrid poplar OP42 (easy-to-root), and used transgenic approaches to verify the role of several transcription factors in the control of adventitious rooting. Increased peroxidase activity was positively correlated with better rooting. We found differentially expressed genes encoding reactive oxygen species scavenging proteins to be enriched in OP42 compared with T89. A greater number of differentially expressed transcription factors in cambium cells of OP42 compared with T89 was revealed by a more intense transcriptional reprograming in the former. PtMYC2, a potential negative regulator, was less expressed in OP42 compared with T89. Using transgenic approaches, we demonstrated that PttARF17.1 and PttMYC2.1 negatively regulate adventitious rooting. Our results provide insights into the molecular basis of genotypic differences in AR and implicate differential expression of the master regulator MYC2 as a critical player in this process. Abstract : Comparative transcriptomic analysis from the cambium of two Populus genotypes with contrasting adventitious rooting phenotype reveals higher transcriptional activity in the easy-to-root compared with the difficult-to-root genotype.